2014
DOI: 10.3109/03014460.2014.967295
|View full text |Cite
|
Sign up to set email alerts
|

VDRpolymorphisms are associated with bone mineral density in post-menopausal Mayan-Mestizo women

Abstract: The results showed that the TT genotype of rs731236 of VDR and one haplotype formed by rs731236 and rs2228570 polymorphisms were associated with higher BMD at TH and FN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…Canto-Cetina i in. oznaczyli obecność polimorfizmu VDR Fok1 i Taq1 u kobiet po okresie menopauzy [45]. U pacjentek z genotypem Tag1 TT stwierdzono wyższe BMD kości biodrowej i w szyjce kości udowej.…”
Section: Wpływ Polimorfizmów Genu Receptora Witaminy D (Vdr) Na Układunclassified
See 1 more Smart Citation
“…Canto-Cetina i in. oznaczyli obecność polimorfizmu VDR Fok1 i Taq1 u kobiet po okresie menopauzy [45]. U pacjentek z genotypem Tag1 TT stwierdzono wyższe BMD kości biodrowej i w szyjce kości udowej.…”
Section: Wpływ Polimorfizmów Genu Receptora Witaminy D (Vdr) Na Układunclassified
“…U pacjentek z genotypem Tag1 TT stwierdzono wyższe BMD kości biodrowej i w szyjce kości udowej. Odmiana Fok1 nie wykazała istotnej zależności [45].…”
Section: Wpływ Polimorfizmów Genu Receptora Witaminy D (Vdr) Na Układunclassified
“…Few candidate gene association studies have been conducted to identify genetic factors contributing to ultrasonography bone parameters (Correa‐Rodríguez, Schmidt‐RioValle, & Rueda‐Medina, ; Correa‐Rodríguez, Schmidt‐RioValle, González‐Jiménez, & Rueda‐Medina, ; Elfassihi et al., ; García‐Ibarbia et al., ; Holliday et al., ; Limer et al., ; Omasu et al., ; Zajickova, Zofkova, & Hill, ). Most work has looked at candidate genes previously associated with BMD phenotypes such as VDR (Boroń et al., ; Canto‐Cetina et al., ), ESR1 (Koller et al., ; Massart et al., ), and WNT16 (Koller et al., ; Zheng et al., ), because no data was available from genome‐wide association studies (GWAS) characterising the genetic factors underlying QUS variability. In 2014, the results of a GWAS meta‐analysis conducted by the Genetic Factors for Osteoporosis (GEFOS) and the Genetic Markers for Osteoporosis (GENOMOS) consortium assessing the genetic determinants of heel bone properties in European subjects were published.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact etiology of osteoporosis still remains poorly understood. In recent years, the vitamin D receptor ( VDR ) gene has been considered as an important candidate gene in the modification and the development of BMD and osteoporosis [ 8 32 ]. The VDR gene contained 14 exons and located on chromosome 12q12–q14, which is a member of the nuclear receptor family of transcription factors [ 11 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morrison et al firstly investigated that genetic variants in the VDR gene could predict spinal and femoral BMD in Caucasian women [ 12 , 13 ]. Since then, a large number of epidemiologic studies have reported the VDR genetic variants (e.g., Fok I (rs10735810), Bsm I (rs1544410), and Apa I (rs7975232)) are associated with BMD and osteoporosis in different ethnic groups [ 8 32 ]. However, to date, there are no published similar studies on the potential relationship of p.Glicine (Gly)14 alanine (Ala) and p.histidine (His) 305 glutanine (Gln) genetic variants in VDR gene with BMD and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%